A high-precision unmanned aerial vehicle positioning system based on ultra-wideband technology. (12th March 2021) - Li, Tian-yu; Duan, Fa-jie; Liang, Chun-jiang; Jiang, Jia-jia; Fu, Xiao; Wang, Qi; Huang, Hui-xiong; Wei, Qi-feng
Abstract: With the help of artificial intelligence technology, the unmanned aerial vehicle (UAV) industry is booming. In the civilian field, a series of fully functional UAV products have emerged one after another, giving birth to a huge industrial chain. To strengthen the UAV market supervision, many countries have introduced a series of standards to regulate UAV products, but they have not yet developed a high-precision positioning system for UAV quality inspection. In this paper, we proposed a high-precision UAV positioning method based on ultra-wideband (UWB) technology. We analyzed the algorithm, base station layout, and clock synchronization to improve the accuracy of the UWB positioning system and established a high-precision UAV trajectory tracking and measurement system based on UWB technology, realizing real-time high-precision positioning of UAVs. Based on the Chan algorithm, we analyzed the base station layout method in combination with the system construction site and proposed a new delay calibration method between positioning base stations. Experimental results show that we have achieved a horizontal accuracy of under 0.1 m and a vertical accuracy of under 0.15 m in a space of 120 m × 60 m × 40 m.